Emerging Comorbidities in Adult Asthma: Risks, Clinical Associations, and Mechanisms - Hannu Kankaanranta; Paula Kauppi; Leena E. Tuomisto; Pinja Ilmarinen (Mediators of Inflammation)
Asthma is a heterogeneous disease with many phenotypes, and age at disease onset is an important factor in separating the phenotypes. Most studies with asthma have been performed in patients being otherwise healthy. However, in real life, comorbid diseases are very common in adult patients. We review here the emerging comorbid conditions to asthma such as obesity, metabolic syndrome, diabetes mellitus type 2 (DM2), and cardiac and psychiatric diseases. Their role as risk factors for incident asthma and whether they affect clinical asthma are evaluated. Obesity, independently or as a part of metabolic syndrome, DM2, and depression are risk factors for incident asthma. In contrast, the effects of comorbidities on clinical asthma are less well-known and mostly studies are lacking. Cross-sectional studies in obese asthmatics suggest that they may have less well controlled asthma and worse lung function. However, no long-term clinical follow-up studies with these comorbidities and asthma were identified. These emerging comorbidities often occur in the same multimorbid adult patient and may have in common metabolic pathways and inflammatory or other alterations such as early life exposures, systemic inflammation, inflammasome, adipokines, hyperglycemia, hyperinsulinemia, lung mechanics, mitochondrial dysfunction, disturbed nitric oxide metabolism, and leukotrienes.